2021
DOI: 10.1021/acs.chemmater.1c02460
|View full text |Cite
|
Sign up to set email alerts
|

Dual-State Emission (DSE) in Organic Fluorophores: Design and Applications

Abstract: Organic luminescent materials have attracted significant attention in the past few years due to their fascinating photophysical properties. Implementing these emissive organic compounds is now being actively pursued in many applications in solution (i.e., sensors, bioimaging) or their solid forms (i.e., optoelectronic devices or data encryption). Despite significant advances in the development of emissive compounds, there has been an increasing quest in the past decade for materials where the emission is prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
81
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(91 citation statements)
references
References 184 publications
(288 reference statements)
0
81
0
Order By: Relevance
“…Recently, a rational molecular design strategy has been presented based on triphenylamine via theoretical calculation and practical verification by the Gong group ( Zou et al, 2022 ). However, although many efforts including various physical and chemical methods have been contributed to designing and exploring new DSE compounds, the research of DSE luminogens remains preliminary with relatively limited examples in the literatures ( Belmonte-Vázquez et al, 2021 ). There still exists a serious lack of a universal molecular design strategy for DSE luminogens.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a rational molecular design strategy has been presented based on triphenylamine via theoretical calculation and practical verification by the Gong group ( Zou et al, 2022 ). However, although many efforts including various physical and chemical methods have been contributed to designing and exploring new DSE compounds, the research of DSE luminogens remains preliminary with relatively limited examples in the literatures ( Belmonte-Vázquez et al, 2021 ). There still exists a serious lack of a universal molecular design strategy for DSE luminogens.…”
Section: Introductionmentioning
confidence: 99%
“…S4†). The relatively weak absorption at around 310 nm in the selected solvents except for acetonitrile (Ace) could originate from the locally excited π–π* transition of TPA units 26 and the major absorption at around 350 nm should correspond to the ICT transition between the TPA unit and the benzaldehyde core. 45 The ICT absorption in solvents remains unchanged with the change of solvent polarity, whereas the fluorescence exhibits obvious solvent-dependent emission.…”
Section: Resultsmentioning
confidence: 99%
“…19 In this regard, π units are often coupled in a conjugated fashion to tune the electronic structures of the molecules, conferring high quantum yields and adjustable emission wavelength on DSEgens. 20 Interestingly, Liu et al reported a tetrahydropyrimidine (THP) compound by connecting multiple isolated aryl arms to a non-conjugated stator and observed strong solid-state emission, despite the absence of effective conjugation between those isolated aryl pendants. 21 We also achieved strong aggregate emission by attaching triphenylamine (TPA) and other aryl groups onto a saturated cyclohexyl ring.…”
Section: Introductionmentioning
confidence: 99%